Tingkat Pencapaian Mahasiswa Melalui Isomorfik Tipe B Pada Topik Satuan - Sudarto Sudarto; Abd. Kadir A (Journal on Education, 2023)
This research is a pre-experimental research conducted to find out the subject knowledge abilities of PGSD FIP UNM Campus VI Bone students who are programming the Elementary Science Basic Concepts course in the even semester of the 2021/2022 academic year on the topic of Units through a type B isomorphic test. The birth of a profile/picture the ability of subject knowledge of PGSD FIP UNM Campus VI Bone students who are programming the Elementary Science Basic Concepts course in the even semester of the 2021/2022 academic year on the topic of Units through the type B isomorphic test is the target to be achieved. To achieve this target, the researcher explored the subject knowledge abilities of the students who were the target subjects by giving a type B isomorphic test. The test was in the form of a written test. The research subjects were PGSD FIP UNM Campus VI Bone students who were programming the Science Basic Concepts Course in the Even Semester of the 2021/2022 Academic Year. Data collection is done by recording test results. The analysis technique uses descriptive analysis. The results showed that students (respondents) who scored in the "very good" category were 25 or 96.2% of people with details of the score, namely: 7 or 26.9% scored 90, 15 or 57.7% scored 85, and 3 or 11.5% get a score of 80. The rest, namely one person or 3.8% get the "good" category. Furthermore, the minimum score obtained by students is 75 (good category), the maximum score is 90 (very good category), the average student score is 85.38 (very good category) with a standard deviation of 3.721. Conclusion: the description of students' subject knowledge abilities on the topic of Units through the type B isomorphic test is that the average ability is in the "very good" category, the range is 75, the minimum score is 75 and the maximum value is 90, the variance is 13,846, and the standard deviation is 3.721 or 4.358% of the average which indicates that the data deviation is less than 5%. That is, the deviation rate of student grade data in this study is very small or negligible.